The relationship between political efficacy and self-rated health: An analysis of Mexican, Puerto Rican, and Cuban subgroups compared to non-Latinx whites in the United States - Anna-Michelle Marie McSorley; Courtney S. Thomas Tobin; Randall Kuhn (Elsevier, 2023)
Latinx represent a growing population in the United States (US) that continue to experience a disproportionate burden of disease. However, health disparities vary across Latinx subgroups, including Mexican, Puerto Rican, and Cuban communities, particularly when assessing self-rated health. Given the nature of political exclusion in the US, these differences may be associated with underexplored political factors, or political determinants of health, within the social environment that distinctly shape health among racial and ethnic minorities. To explore potential pathways that connect the political environment to individual-level health outcomes among Latinx subgroups, political efficacy (or one's perceptions about one's power to influence political affairs) was assessed as a correlate of self-rated health. We used secondary data from the 2016 Collaborative Multiracial Post-election Survey to conduct ordered logistic regression analysis to determine whether two domains of political efficacy, internal and external political efficacy, were correlates of self-rated health among Mexican, Puerto Rican, and Cuban subgroups as compared to non-Latinx whites in the US. We also tested for differential associations across Latinx subgroups as compared to non-Latinx whites. The sample consisted of 3156 respondents (1486 Mexicans, 484 Puerto Ricans, 159 Cubans and 1027 non-Latinx whites). Among Puerto Ricans, results revealed that lower levels of internal political efficacy were associated with higher levels of self-rated health. Conversely, among other subgroups, positive associations between internal political efficacy and self-rated health were observed. This study provides empirical evidence of a relationship between internal political perceptions and health perceptions that has not previously been established within the Latinx health disparities literature. Future investigations should continue to examine pathways that connect political determinants to individual-level health outcomes, particularly among communities that disproportionately experience political exclusion.